Zakat Komoditas Pertanian Dalam Perspektif Hermeneutika Etik - Arif Al Wasim (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2017)
Zakat is seen as one of solutions to the community socio-economic problems, in this case the distribution of welfare and poverty alleviation. Looking at the context of contemporary Indonesia, zakat for agricultural commodities seems to need a review to be able to find its relevance. The majority of farmers who cultivate staple food crops in Indonesia are generally still in the middle to lower economic class, even at the poverty threshold. Hermeneutics is a scientific instrument that has a primary function as a means to better understand texts, symbols and phenomena. With a better understanding of religious texts and phenomena, an important point will be obtained to find the contextuality of religious teachings for today's life. In the perspective of Paul Ricoeur's ethical hermeneutics, zakat can be understood as a religious ritual based on a spirit of togetherness towards independence. The principle of equitable welfare distribution and professional equality, fosters ethical awareness of the need for the remodeling of niṣâb, so that agricultural commodities have an equivalent value to other commodities in modern economic life. The need for the re-contextualization of the formulation of zakat is an effort to find a meeting point for equality and balance of farmers in industrial society.